Africa and the challenges to democratisation. (1st January 2014) - Mapuva, Jephias
Democratisation process in Africa has been under increasing threat from despotic political leaders who have failed to contend with the sweeping forces of globalisation demanding for the opening up of political space. Armed with claims of the liberation struggle, most of them failed to provide for their people with many incidences of high poverty levels, and high illiteracy rates among the grassroots people. A strong prodemocracy wind that has swept across the continent has been viewed with suspicion by most African leaders who perceive it as Western attempts at neo-colonialism. This has further compromised the relationship between the state and civil society as governments have accused civil society of being conduit to destabilise African countries. The continued existence of ex-dictators in active politics or in influential positions in many African countries, have remained a threat to the restoration or deepening of democratic institutions within the African continent.